Persistent pulmonary hypertension of the newborn (PPHN): What can we do in low resource setting? - Hasan, Taufiq Hidayat; Abu Bakar, Asrar; Anuar, Muhamad Azamin; Syed Abd Hamid, Syed Abdul Khaliq; Mohamed, Mossad Abdelhak Shaban (2019)
Background Persistent pulmonary hypertension of the newborn remains a challenging problem in neonates. Some cases may be severe and not responsive to conventional respiratory support. Inhaled nitric oxide and extracorporeal membrane oxygenation have improved outcome, but these modalities are expensive and unavailable at most hospitals in Malaysia.